Simulation of extreme Indian summer monsoon years in Coupled Model Intercomparison Project Phase 5 models: Role of cloud processes. (10th September 2018) - Chaudhari, Hemantkumar S.; Hazra, Anupam; Pokhrel, Samir; Saha, Subodh Kumar; Talluri, Sai Sruthi
Abstract : The Indian summer monsoon (ISM) is a climate coupled system where cloud processes play a significant role in modulating the thermodynamics and dynamics of the atmosphere. The realistic representation of cloud by coupled model becomes indispensable for the simulation of the rainfall variability dictating the extreme ISM rainfall years. This study pinpoints the importance of correct representation of cloud processes and different types of rainfall in coupled climate model for the realistic simulation of monsoon extreme rainfall years. The study has used historical runs of Coupled Model Intercomparison Project Phase 5 (CMIP5) models. It provided best opportunity to investigate the ISM rainfall characteristics in case of anomalous monsoon and associated physical processes responsible for the modulation of large‐scale circulation. The study has identified the mechanism behind the better simulation of anomalous years. Relatively more cloud condensate at upper level and middle level is present in excess monsoon years. Pertaining to phase changes and thermodynamical processes, there will be relatively more tropospheric temperature gradient and it will be conducive for strong monsoon. Proper representation of convective and stratiform rain is seen during extreme years. Precipitable water is also relatively more during excess monsoon years. As a result, total rainfall also enhances and it leads to excess monsoon. In contrast, during deficient monsoon relatively less cloud condensate at upper level and middle level is present. Therefore, the correct representation of cloud condensate vertical profile and stratiform/convective rain are crucial for the better simulation of excess and deficient monsoon, which may further improve the variability of ISM in climate model. This study connotes the urgent need of the improvement of cloud parameterization in coupled climate models for the betterment of monsoon variability and realistic representation of deficient/excess monsoon rainfall patterns over Indian subcontinent. Abstract : Total mean rainfall (June–September: JJAS; unit: mm/day) for CMIP5 models (a–g) and GPCP (h).